Dental erosion among South Brazilian adolescents: A 2.5‐year longitudinal study. Issue 1 (20th July 2017) - Brusius, C.D.; Alves, L.S.; Susin, C.; Maltz, M.
Abstract: Objectives: This population‐based longitudinal study investigated the incidence, progression and risk factors for dental erosion among South Brazilian adolescents. Methods: Eight hundred and one schoolchildren attending 42 public and private schools were clinically examined at 12 years of age; clinical examinations were repeated after 2.5 years (SD=0.3). After tooth cleaning and drying, permanent incisors and first molars were classified using the Basic Erosive Wear Examination (BEWE) scoring criteria. Questionnaires were used to collect data on socio‐demographic characteristics, dietary habits, toothbrushing frequency and general health. Poisson regression analysis was used to assess the association between dental erosion incidence and explanatory variables, with adjusted incidence risk ratios (IRR) and 95% CI estimated. Results: Among those who did not have dental erosion at baseline, 49 of 680 schoolchildren (7.1%; 95% CI=5.2‐9.1) developed erosive lesions over the follow‐up period. Among schoolchildren who had dental erosion at baseline, 31 of 121 (25.4%; 95% CI=17.6‐33.3) had new or more severe lesions. Boys were more likely to develop dental erosion than girls (IRR=1.88; 95% CI=1.06‐3.32). Conclusions: A moderate incidence of dental erosion was observed among South Brazilian adolescents, with boys being at higher risk. The high progression rate of 25% observed here is very concerning, and it should be taken in consideration when designing preventive strategies for dental erosion.